Diminishing Marginal Utility of Technological Devices toward Academic Performance in Mathematics, Reading, and Science - Martos , Gerald; Jose, David S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The Philippines, in its pursuit of aligning its education system with global standards, has participated in the Program for International Student Assessment (PISA) which evaluates 15-year-olds' reading, scientific, and mathematical proficiency. However, the 2022 PISA report ranked Filipino learners among the lowest five in reading, science, and mathematics. This study explores how ownership of technological devices influences student performance in these domains. Using Ordinal Logistic Regression, we analyze the 2022 PISA ordinal data for 7608 Filipino students. Results show a diminishing marginal return on academic achievement as device ownership increases. While initial access to technology boosts performance, the effect weakens as students own more devices. This trend is stronger among learners without siblings and persists regardless of internal or external digital distractions. Findings emphasize the need for balanced digital engagement. Rather than restricting access or full enablement, families and policymakers should focus on strategic technology use to enhance education, aligning with Sustainable Development Goals for quality learning.